Analisis Penerapan Akuntansi Tentang Aset Tidak Berwujud Pada Bisnis Waralaba Anemone - Citradewi, Ni Komang Tri; Lesmana Putra, I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2025)
This study aims to analyze and understand the application of accounting for intangible assets in franchise businesses. The research employs a qualitative method by examining accounting practices based on SAK EMKM Chapter 12 on Intangible Assets. The study was conducted at Anemone Dajan Peken Tabanan with the franchise manager as the informant. Data were collected through observation, interviews, and document study. Data analysis was carried out through data collection, data reduction, data presentation, and conclusion drawing. The findings show that intangible assets such as trademarks, learning systems, teaching module copyrights, goodwill, and franchise licenses play an important role in Anemone’s business. However, the accounting practices at Anemone Dajan Peken remain simple and do not fully comply with SAK EMKM Chapter 12. The franchise fee, which should be recognized as an intangible asset and amortized over five years, was instead fully expensed in the year the transaction occurred, causing the financial information presented to inadequately reflect the actual condition of the business.